2010
DOI: 10.1186/1447-056x-9-10
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics in patients with headache in an outpatient clinic in Japan

Abstract: BackgroundLittle is known about the prevalence of primary and secondary headache in clinics in Japan. The aim of this study is to characterize patients with headache in an outpatient unit where primary care physicians are working in Japan.MethodsConsecutive outpatients who newly visited the Department of General Medicine, Asahikawa Medical College Hospital, Asahikawa, Japan between April 2005 and March 2009 were analyzed. Each parameter such as age, sex or diagnosis was investigated.ResultsOut of 4693 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
6
8
0
Order By: Relevance
“…In an article by Takeshima et al [6] from Japan, the prevalence was 21.8% from 15-29 years, 26.8% from 30-39 years, 26.5% from 40-49 years, 21.5% from 50-59 years and 17.8% in those 60 years and older [6]. Similar results have [7,8]. As we found in our research, TTHA was mostly seen in the 3 rd -4 th decades and showed a decline after those ages.…”
Section: Discussionsupporting
confidence: 64%
“…In an article by Takeshima et al [6] from Japan, the prevalence was 21.8% from 15-29 years, 26.8% from 30-39 years, 26.5% from 40-49 years, 21.5% from 50-59 years and 17.8% in those 60 years and older [6]. Similar results have [7,8]. As we found in our research, TTHA was mostly seen in the 3 rd -4 th decades and showed a decline after those ages.…”
Section: Discussionsupporting
confidence: 64%
“…Primary headaches were diagnosed in 87.8% of the patients and secondary headaches and painful cranial neuropathies/other facial pains were diagnosed in 8.3% and 1.7% of patients. This distribution of headaches was similar to the results of previous studies conducted in specialized headache clinics and had a higher ratio of primary headaches than that in studies conducted in general neurology or emergency departments ( 2 9 11 23 24 ).…”
Section: Discussionsupporting
confidence: 87%
“…ICHD-3β is better than ICHD-2 in the area of other primary headaches and CM ( 5 25 26 ). According to other ICHD-2-based studies, other primary headaches accounted for 1.5-5.9% of all headaches ( 2 9 11 23 ). In this study, other primary headaches were very commonly diagnosed with ICHD-3β, with the percentage being 16.3%.…”
Section: Discussionmentioning
confidence: 91%
“…Primary headache was the most common type treated by both hospitals. The proportions of migraine headache and TTH among the treated populations were similar, as was also the case in a Japanese study . Although trigeminal autonomic cephalgia was extremely rare, the prevalence of this condition was higher than suggested by the epidemiological survey .…”
Section: Developments In Headache Care In Chinasupporting
confidence: 76%